Picturing the Underserved Audience: Photovoice as Method in Applied Communication Research - Abigail S. Borron (Journal of Applied Communications, 2013)
The use of photographs in sociology and anthropology has grown over the last half of the 20th century, leading to various photo-based research methods that are intended to aid in building and enriching participant narratives. One specific photo-based method, known as photovoice, was developed for the purposes of enabling community members to capture photographs themselves in order to gain a deeper understanding of participant culture. In addition, it has the ability to visually portray and share experiences and knowledge about issues that otherwise would be difficult to explain through in-depth interviews alone. This professional development paper demonstrates the value of incorporating photovoice into a multi-method research project in the field of applied communications for the purposes of gaining valuable insights into the lived experiences of underserved audiences. Drawing from a larger study examining the culture of participants within the Extension-led Expanded Food and Nutrition Education Program (EFNEP), the results and discussion demonstrate that photovoice helps to function as a checkpoint in knowledge production and ways of knowing on behalf of the researcher. In addition, photovoice as method demonstrates an effort that can improve and diversify the field of applied communication research, especially as it relates to the National Research Agenda’s priority of addressing vibrant and resilient communities.
Keywords: Photovoice; underserved audiences; qualitative researcher; culture; cross-disciplinary understanding